That was then, this is now - Hinton, Susan Eloise (Puffin Books, 1998)
Sixteen-year-old Mark and Bryon have been like brothers since childhood, but now, as their involvement with girls, gangs, and drugs increases, their relationship seems to gradually disintegrate.
Keywords: Social problems / Fiction; Friendship / Fiction; Social problems / Juvenile fiction; Friendship / Juvenile fiction; Jugendbande; Slum; USA; Jugendbuch